Management of dermatophytosis of nail and hair - Archana Singal; Manasa Narayan Kayarkatte (Wolters Kluwer Medknow Publications, 2017)
Dermatophyte infections are common worldwide, and dermatophytes are the prevailing causes of fungal infection of the skin, hair, and nails. These infections lead to a variety of clinical manifestations; nail infection known as onychomycosis (OM) and hair infection as Tinea capitis. The diagnosis and treatment of dermatophyte infections of the Nail and hair will be reviewed here.